Meningkatkan Keterampilan Servis Atas Dalam Permainan Bola Voli dengan Pendekatan Pembelajaran Drill - Taslim, Zailan (Jurnal PGSD, 2020)
This study aims to find out about the ability or skills of class V students of elementary school 132 Rejang Lebong in servicing volleyball can be improved through the learning method of drill. In accordance with these problems, this study uses Classroom Action Researchw hich is carried out in two cycles and in that cycle there are planning, action, observation/reflection, and reflection. The sample/subject of this study were students at elementary school 132 Rejang Lebong, totaling 19 students. In the final test, collect data from cycle 1 and cycle 2 using the service skill test instrument for volleyball. From several inter-cycle test result obtained learning outcomes data from cycle 1 and cycle 2 there has been an increase of between 40% to 90%. Based on the result of data analysis and discussion it can be concluded that the drill and play approach can improve the ability to service volleyball at elementary school 132 Rejang Lebong. It is recommended that sports educators can implement the drill and play approach, as they are proven to able to improve service learning outcomes for volleyball.